The portuguese medieval parliament : are we asking the right questions? - Duarte, Luís Miguel (2003)
It had traditionally been thought that the history of the Portuguese mediaeval parliament was exhausted from the point of view of available information; almost all approaches had studied the Cortes from a legal angle. In 1990, Armindo de Sousa published As Cortes Medievais Portuguesas (1385-1490); this work was to radically renew everything that was known about the theme, proving that, even from the strictly factual point of view, there continued to be a large number of errors and gaps and, above all, suggesting a sociological and political approach to the mediaeval parliament, treating the texts that were produced at the Cortes as discourses, rejecting biologistic theories and concepts such as nature and decadence, lingering in particular over the study of the primary and secondary functions of parliament. But this book, which represented a complete break with everything that had previously been written on the theme, did not provoke any significant reaction either in Portugal or in other countries, being received in virtual silence. Thirteen years after its publication, this article seeks to rekindle discussion about the more controversial and innovative aspects of Armindo de Sousa’s thesis, as well as updating it in regard to a number of aspects and putting forward a new agenda for research into the Portuguese mediaeval parliament.